Will Islamic Banking make the World less risky? An Empirical Analysis of Capital Structure, Risk Shifting and Financial Stability - Moazzam Farooq; Sweder van Wijnbergen; Sajjad Zaheer (Tinbergen Institute, 2015)
We use a classic Merton credit risk framework to argue that Islamic Banking Institutions (IBIs) face less incentive to take on risks than Conventional Banking Institutions (CBI). IBIs have less incentive for risk shifting both in and outside of distress situations. We test and confirm this prediction in an empirical analysis based on a dataset covering all CBIs, IBIs, and Islamic and conventional subsidiaries of mixed banking institutions in Pakistan. We find that full-fledged Islamic banks (IBs) are indeed more stable than conventional banking institutions (CBIs), and are better capitalized than their conventional counterparts. IBIs also have less volatile asset returns, less non-performing loans (NPLs) and lower loan loss provisioning. Similar results obtain for Islamic windows of mixed banks compared with conventional windows. The analysis suggests that the loss absorption capacity of Islamic banks leads to less risk taking and a more stable banking system.
Keywords: G02; G21; Z12; 330; Islamic Banking; risk shifting; asset quality; financial stability